Diagnóstico socioeconómico de los propietarios de establecimientos de belleza en el sector centro La Aurora, cantón Daule, provincia del Guayas- Ecuador - Pazmiño Iñiga, Leslie Francisco (2022)
The objective of this work is to analyze the socioeconomic situation of the owners of beauty establishments, in the downtown sector of La Aurora, Canton Daule, province of Guayas during the COVID-19 pandemic. The method applied is the non-probabilistic sampling for convenience, in which 60 beauty establishments of the before mentioned sector were identified and its purpose is to analyze the economic and social impacts that it has had on the beauty establishments during and after the health emergency. The research approach is mixed, both qualitative and quantitative, which allows us to visualize the great loss of employment in this sector, the reduction of clients that impacted more than 40% of sales, the lack of economic support for microentrepreneurs and the importance that social networks and technology took on in order to sustain the establishments; As a result of this, it is concluded that despite not being trained in the face of these catastrophes, the beauty sector has proposed solutions to seek to reactivate itself through strategic measures in order to improve local development.